The Influence of Instagram Social Media Marketing as a Promotional Means to Increase Intentions to Visit Tourist Destinations - Fitri, Fadhilla Resta; Februadi, Agustinus C.; Elisabeth, Vera; Yuardani, Ade Muhamad (Politeknik Negeri Bandung, 2023)
Technological advances, mainly social media, can drive the increase in GDP. The ease, convenience, and practicality of consumers using social media create almost limitless opportunities for social media marketing in the travel sector. Tourism destination managers have widely used Instagram to promote their destinations by creating appropriate images. However, it is essential to understand the types of destination images that influence tourists. This research aims to understand the relationship between destination image and intention in social media marketing. This research also aims to determine which cognitive or affective destination description is more significant. This research involved 373 respondents who actively use Instagram and know tourism destinations' official social media accounts. The data was analyzed using PLS-SEM. This research finds that social media marketing significantly affects the intention to visit, affective, and cognitive destination images. Destination image also mediates the relationship between social media marketing and visitors' propensity to leave. The analysis findings also show that affective destination image is more effective than cognitive destination image in influencing visitor intentions. These results highlight the importance of considering emotional components when promoting tourist locations.